2007
DOI: 10.1111/j.1365-2265.2007.02773.x
|View full text |Cite
|
Sign up to set email alerts
|

Metastases to the thyroid gland: prevalence, clinicopathological aspects and prognosis: a 10‐year experience

Abstract: TM is a rare event, is more frequent in patients older than 60 years, and has the same impact on prognosis as nonthyroidal metastases. Although thyroidectomy may be useful to avoid further dissemination of the primary tumour in case of solitary TM, it does not contribute to prolonging patient's life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
277
7
8

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 213 publications
(297 citation statements)
references
References 30 publications
5
277
7
8
Order By: Relevance
“…Oncological patients represented only 6.3% of that population, in contrast to centres specialising in the diagnosis and treatment of cancers that present many reports on metastases to the thyroid gland [13,[27][28]. Probably for this reason, in our study the percentage of patients with secondary cancer (0.3%) was lower than in typical oncological centres, and similar to that found in centres involved in the diagnosis of thyroid disorders [15,25] and in general centres (non-specialised) [8] (Table IV). Regardless of that fact, our data showed regularity in higher risk of metastasis in patients with malignant disease than in those with negative history of cancer.…”
Section: Prace Oryginalnecontrasting
confidence: 50%
See 3 more Smart Citations
“…Oncological patients represented only 6.3% of that population, in contrast to centres specialising in the diagnosis and treatment of cancers that present many reports on metastases to the thyroid gland [13,[27][28]. Probably for this reason, in our study the percentage of patients with secondary cancer (0.3%) was lower than in typical oncological centres, and similar to that found in centres involved in the diagnosis of thyroid disorders [15,25] and in general centres (non-specialised) [8] (Table IV). Regardless of that fact, our data showed regularity in higher risk of metastasis in patients with malignant disease than in those with negative history of cancer.…”
Section: Prace Oryginalnecontrasting
confidence: 50%
“…Similarly, other authors indicate that metastases to the thyroid gland usually involve people in the 6th-7th decade of life [8,11,14,32]. On the other hand, the youngest patient with metastasis in our study was 25 years old (infiltration of the thyroid was the first sign of cancer), and Pusztaszeri et al showed clear cell sarcoma metastasis in a sevenyear-old child [14].…”
Section: Prace Oryginalnementioning
confidence: 61%
See 2 more Smart Citations
“…Some studies suggest a higher incidence in females, while others report otherwise (4,12,13). According to their primary site, melanomas are grouped as cutaneous, ocular, mucosal, and of unknown origin; of all, mucosal melanomas are the least frequent ones (14).…”
Section: Discussionmentioning
confidence: 98%